2022
DOI: 10.5507/bp.2022.035
|View full text |Cite
|
Sign up to set email alerts
|

Skin manifestations of pancreatic diseases

Abstract: Although symptoms of pancreatic diseases such as pancreatitis, acute and chronic and, carcinoma of the pancreas are mainly gastrointestinal in nature, the extra-pancreatic symptoms are also important. These include skin symptoms, such as pancreatic panniculitis, acanthosis nigricans, livedo reticularis, necrolytic migratory erythema, cutaneous signs of hemorrhage, as in persons with severe acute pancreatitis, or the finding of cutaneous metastases of pancreatic carcinoma, which may be a sign of advanced diseas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…Although the pathogenesis of pancreatic panniculitis is not fully understood, it is hypothesized that the release of high amounts of pancreatic enzymes may lead to a focal necrosis of lipids with an accompanying inflammatory reaction [1]. It has also been suggested that additional factors are necessary for the development of pancreatic panniculitis such as increased vessel permeability as this allows the pancreatic enzymes to enter the circulation and into subcutaneous fat [2]. Treatment of pancreatic panniculitis is mostly supportive and aims to target any underlying pancreatic pathology [1].…”
Section: Case Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although the pathogenesis of pancreatic panniculitis is not fully understood, it is hypothesized that the release of high amounts of pancreatic enzymes may lead to a focal necrosis of lipids with an accompanying inflammatory reaction [1]. It has also been suggested that additional factors are necessary for the development of pancreatic panniculitis such as increased vessel permeability as this allows the pancreatic enzymes to enter the circulation and into subcutaneous fat [2]. Treatment of pancreatic panniculitis is mostly supportive and aims to target any underlying pancreatic pathology [1].…”
Section: Case Discussionmentioning
confidence: 99%
“…The first case of pancreatic panniculitis was initially described by Chiari in 1883, characterized by necrosis of subcutaneous fat [1][2][3]. This entity continues to be a rare manifestation today, occurring with higher incidence in middle-aged male patients with a history of alcoholism [1].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other extra pancreatic manifestations that have been described in association with pancreatitis include panniculitis, polyarthritis (PPP) syndrome [ 13 ]. Cutaneous manifestations reported with pancreatitis include acanthosis nigricans, necrolytic migratory erythema, livedo reticularis and hemorrhagic skin lesions seen in severe acute pancreatitis (AP) [ 14 ]. Other symptoms that have been described with AP include fatigue [ 13 ], abdominal wall abscess and epididymoorchitis [ 15 ].…”
Section: Introductionmentioning
confidence: 99%